Evaluation of Arabic Language Learning Assessment Using CBT Application at Muhammadiyah 4 High School in Jakarta with the CIPP Model - Rachman, Addif Zikri; Nugrahawan, Ahmad Rizki (UIN Sultan Aji Muhammad Idris Samarinda, 2024)
The use of Computer-Based Tests (CBT) in assessing Arabic language learning at SMA Muhammadiyah 4 Jakarta has been the primary focus of this research. The study aims to evaluate the effectiveness of CBT implementation using the Context, Input, Process, and Product (CIPP) evaluation model. A qualitative descriptive approach was employed, utilizing data collection techniques such as questionnaires, interviews, observations, and document analysis. The evaluation results indicate that CBT has had a positive impact on enhancing the efficiency, speed, and accuracy of assessments, despite encountering challenges such as infrastructure readiness and technical training. From the perspectives of both students and teachers, the experience of using CBT has generally been positive, although there is a recognized need for improved facility support and deeper technical training. This evaluation suggests the necessity for ongoing school support to ensure the long-term success of CBT implementation.